FREQUENCY OF RETINAL REDETACHMENT BASED ON THE PRIMARY REATTACHMENT TREATMENT AND INTRAOCULAR TAMPONADE - A M Ichsan; Erwin Iskandar; Rova Virgana; Arief Kartasasmita; Habibah S. Muhiddin (Faculty of Medicine, Hasanuddin University., 2017)
ABSTRACT Introduction: To observe the number and presentation of retinal redetachment after primary reattachment treatment in a national eye center. Methods: This study was designed for ob- servational-descriptive of the medical record from April 2011 to March 2012. Selected cases were identified on the secondary retinal surgery for retinal reattachment followed the failure of the primary treatment. Cases were then classified into 4 groups based on the primary reattach- ment procedure: pneumatic retinopexy (PR), scleral buckle (SB), pars plana vitrectomy (PPV), and combined SB with PPV. Furthermore, in the group of PPV and SB+PPV were then divided into 3 subgroups based on the intraocular tamponade: SF6 gas, silicone oil, and heavy silicone oil. Results: At one-year followed-up data, the presentation retinal redetachment was 7.1%, relative to the sex female (26%) was less than male (74%) with the most common age group was 41-50 years-old. Regarding with primary reattachment treatment, cases of retinal redetachment after pneumatic retinopexy was 6%, the scleral buckle was 16%, pars plana vitrectomy was 29%, and combined sclera buckle with pars plana vitrectomy was 48%. Con- clusions: Rates of retinal redetachment after primary reattachment treatment varied from 6% to 48%, that were performed by combined scleral buckling and pars plana vitrectomy with or without tamponade silicone oil. Keyword : Retinal redetachment, pars plana vitrectomy, scleral buckle, silicon oil, intraocular gas